Pengaruh Kualitas Produk dan Harga terhadap Kepuasan Pelanggan Mie Gacoan Dr. Mansyur Medan - Nabila Malona Siregar; Agus Edi Rangkuti; Annalisa Hasibuan; Ika Mary Pasaribu; Parenta Ritonga (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
In the current era of globalization, the business world is experiencing rapid growth, particularly in the culinary industry. This business is directly related to the basic human need for food, as it is one of the fundamental necessities for survival. The influence of product quality and price on customer satisfaction at Mie Gacoan Dr. Mansyur Medan has become an interesting topic for research, given the importance of these two factors in maintaining and enhancing customer satisfaction. This study aims to determine the extent to which product quality and price affect customer satisfaction at Mie Gacoan in Medan, with a focus on students of the Business Administration Department at Politeknik Negeri Medan as the research subjects. This study employs a quantitative research method with a descriptive approach, including tests for validity, reliability, classical assumptions, hypothesis testing (t-test, F-test, and analysis of the coefficient of determination (adjusted R square)). Data analysis techniques were performed using multiple linear regression analysis with SPSS version 26, involving 100 respondents. Data collection was carried out through questionnaires and literature studies. The results of the study show that product quality (X1) and price (X2) have a positive and significant influence on customer satisfaction (Y), both partially and simultaneously. The results of the multiple linear regression analysis reveal that the price variable has a greater or more dominant influence on customer satisfaction, with a regression value of 76.9% compared to the product quality variable, which obtained a value of 16.9%. Additionally, the results of the coefficient of determination test (adjusted R square) indicate that the variables of product quality and price can explain 81.3% of the influence on customer satisfaction, while the remaining 18.7% is influenced by other variables not examined in this study, such as service quality, ambiance, promotion, and other variables.